Mechanical properties of all-suture anchors for rotator cuff repair - Nagra, N; Zargar, N; Smith, R; Carr, A (British Editorial Society of Bone and Joint Surgery, 2017)
Objectives All-suture anchors are increasingly used in rotator cuff repair procedures. Potential benefits include decreased bone damage. However, there is limited published evidence for the relative strength of fixation for all-suture anchors compared with traditional anchors. Materials and Methods A total of four commercially available all-suture anchors, the ‘Y-Knot’ (ConMed), Q-FIX (Smith & Nephew), ICONIX (Stryker) and JuggerKnot (Zimmer Biomet) and a traditional anchor control TWINFIX Ultra PK Suture Anchor (Smith & Nephew) were tested in cadaveric human humeral head rotator cuff repair models (n = 24). This construct underwent cyclic loading applied by a mechanical testing rig (Zwick/Roell). Ultimate load to failure, gap formation at 50, 100, 150 and 200 cycles, and failure mechanism were recorded. Significance was set at p ≺ 0.05. Results Overall, mean maximum tensile strength values were significantly higher for the traditional anchor (181.0 N, standard error (se) 17.6) compared with the all-suture anchors (mean 133.1 N se 16.7) (p = 0.04). The JuggerKnot anchor had greatest displacement at 50, 100 and 150 cycles, and at failure, reaching statistical significance over the control at 100 and 150 cycles (22.6 mm se 2.5 versus 12.5 mm se 0.3; and 29.6 mm se 4.8 versus 17.0 mm se 0.7). Every all-suture anchor tested showed substantial (> 5 mm) displacement between 50 and 100 cycles (6.2 to 14.3). All-suture anchors predominantly failed due to anchor pull-out (95% versus 25% of traditional anchors), whereas a higher proportion of traditional anchors failed secondary to suture breakage. Conclusion We demonstrate decreased failure load, increased total displacement, and variable failure mechanisms in all-suture anchors, compared with traditional anchors designed for rotator cuff repair. These findings will aid the surgeon’s choice of implant, in the context of the clinical scenario.